2017
DOI: 10.22159/ajpcr.2017.v10i7.18725
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and in-Vitro-in-Vivo Evaluation of Alginate-Chitosan Microspheres of Glipizide by Ionic Gelation Method

Abstract: Objective: This work is aimed to formulate and evaluate alginate-chitosan microspheres of glipizide for the effective use in the treatment of diabetes.Methods: Sustained release (SR) microspheres were prepared by gentle mixing of polymers in water with the drug by agitation. The polymers used were sodium alginate and chitosan, which was extruded into 5% calcium chloride solution to produce microspheres by ionic gelation method.Results: Single unit dosage form of glipizide causes gastric irritation. When conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Alginate is highly hydrophilic that can form stable hydrogels in the presence of certain divalent cations, such as Ca2+, Mg2+, Fe2+, Ba2+, or Sr2+. Ca2+ is one of the most commonly used divalent cations to ionically crosslink with alginate [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Alginate is highly hydrophilic that can form stable hydrogels in the presence of certain divalent cations, such as Ca2+, Mg2+, Fe2+, Ba2+, or Sr2+. Ca2+ is one of the most commonly used divalent cations to ionically crosslink with alginate [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphology of microbeads was explored using SEM (USA model). A known quantity of dried alginate beads were placed or spread on a brass stub using double-sided adhesive tape and made electrically conductive by coating with a thin layer of gold, and SEM images were seen at various accelerating voltage [15,16]. These test samples were then randomly scanned, and photomicrographs were taken care.…”
Section: Sem Studiesmentioning
confidence: 99%
“…Carboxymethyl cellulose in conjunction with sodium alginate in equal proportions with different curing agents naming aluminum chloride (LF8), barium chloride (LF17), and calcium chloride (LF18) at same concentration, i.e., 5% w/v to modulate drug loading, shape, surface, and drug release kinetics profile in sustained manner [23,24]. After 2 h of dissolution studies, drug release in 0.1N HCL buffer medium was found to be at rate of 16 In initial span of 2 h. The intensity of swelling of beads is to a minimum extent in the presence of acidic medium, which is due to alginate was protonated into insoluble form of alginic acid and the creation of intermolecular and intra molecular hydrogen bonding between the two used polymers, the less swelling should reduce the matrix permeability and limit the drug diffusion at acidic atmosphere and the force of H 2bond is more noteworthy than the repulsive forces, the microbeads are kept in a contracted state in acidic medium, and the alginate microspheres shrink due to tightening of the gel meshwork and the drug is discharged slowly. The rate of swelling is significantly increased than acidic medium (0.1N HCL).…”
Section: Dissolution Studiesmentioning
confidence: 99%
“…One recent study reported the oral administration of LID HCL prior to anesthesia for laparoscopy. 18 Other research studies have described the oral delivery of microspheres, consisting of Alginate (ALG) and Chitosan (CS) as mucoadhesive polymers. These microspheres were successfully combined with various drugs, such as glipizide, 19 insulin, 20 ranitidine, 21 metformin, 22 diclofenac, 23 and various other drugs, 24 and showed improved solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%